Thermochemical batteries using metal carbonates: A review of heat storage and extraction - Desage, Lucie; McCabe, Eleanor; Vieira, Adriana P.; Humphries, Terry; Paskevicius, Mark; Buckley, Craig E. (2023)
The development of energy storage systems is essential for the full deployment of renewable energy technologies. Heat storage through high-temperature thermochemical reactions is promising for integration into power production plants. Metal carbonates, particularly calcium carbonate, have attracted interest due to their high thermochemical energy storage capacity and economic appeal. The thermochemical energy storage process involves the endothermic storage of heat when a metal carbonate decomposes into a metal oxide and carbon dioxide gas. Exothermic heat generation is possible by allowing carbon dioxide to react with the metal oxide to reform the metal carbonate. In recent decades multiple prototype installations based on these materials have been tested; however, a drastic loss in energy storage capacity is often encountered. The use of additives, such as aluminates, silicates, zirconates, and titanates, has been shown to improve the cycling performance of the thermochemical storage material. A complete thermochemical battery comprises a thermochemical reactor for both thermal charging and discharging, may include a heat extraction system to remove or deliver heat to the storage material, and must also integrate a carbon dioxide storage unit combined with a thermocline device to store and recover thermal energy from the carbon dioxide gas as required. Several carbon dioxide storage options are available, including compression, physisorption, low-temperature metal oxides and metal-organic frameworks. Carbon dioxide storage systems and thermoclines are usually selected for their thermophysical, economic, and environmental properties. Often, numerical modelling is used to optimise the design of the entire system. This review article details the recent advances made on each aspect of the thermochemical battery, including metal carbonates as heat storage materials and existing large-scale installations, heat extraction systems, development of thermoclines, carbon dioxide storage, and also discusses exergy analysis models to evaluate these systems.